Uptake of core outcome sets by clinical trialists in China: a protocol [version 2; peer review: 2 approved] - Paula Williamson; Hongcai Shang; Zhuo Chen; Mike Clarke; Shuling Liu; Xiaodan Fan; Wenhui Wang; Ruijin Qiu (F1000Research, 2024)
Background The concept of core outcome sets (COS) has been introduced in China for about 10 years. In recent years, some Chinese researchers also committed to developing COS, though the majority of COS are ongoing. However, there were more than 500 published COS for research in the COMET database by 2020. The extent of availability of COS for the top 25 diseases with the highest burden in China is unknown. In addition, the uptake of COS in clinical trials for these diseases is unknown, along with the knowledge, perceptions, and views of the clinical trialist community in China on the use of COS in relation to choosing outcomes for their research. Methods The main burden of disease in China will be identified. Then we will search the COMET database to identify if there are ongoing or completed relevant COS research A COS published since 2012 would be preferred to one published before 2012 for the analysis of COS uptake if one meets the eligibility criteria. We will extract scopes of published eligible COS, including condition, population, interventions, and core outcomes. Then we will search the Chinese Clinical Trial Registry using disease names for each disease that has a published COS. We will assess the overlap in scope between clinical trials and COS. Then we will conduct an online survey and semi-structured interviews to identify the knowledge and perceptions of COS among primary investigators of included clinical trials. Discussion This research will fill in gaps between COS and the burden of disease in China. Understanding clinical trialists’knowledge and perceptions of COS may help dissemination and application of COS in the future. Trial registration This research is registered in Core Outcome Measures in Effectiveness: https://www.comet-initiative.org/Studies/Details/2563.